What is the price for the Duchenne gait pattern in patients with cerebral palsy? - Salami, Firooz; Thielen, Mirjam; Krautwurst, Britta; Dreher, Thomas; Wolf, Sebastian Immanuel (Gait & posture, 2017)
Duchenne gait is characterized by trunk lean towards the affected stance limb with the pelvis stable or elevated on the swinging limb side during single limb stance phase. We assessed the relationship between hip abduction moments and trunk kinetics in patients with cerebral palsy showing excessive lateral trunk motion. Data of 18 subjects with bilateral spastic cerebral palsy (CP) and 20 aged matched typically developing subjects (TD) were collected retrospectively. Criteria for patient selection were barefoot walking without aid presenting with excessive lateral trunk motion. Subjects had been monitored by conventional 3D gait analysis of the lower extremity including four markers for monitoring trunk motion. Post-hoc, a generic musculoskeletal full body model (OpenSim 3.3) assuming a rigid trunk articulated to the pelvis by a single ball joint was applied for analyzing joint kinematics and kinetics of the lower limb joints including this spine joint. Joint angle ranges of motion, maximum joint moments and powers in the frontal plane as well as mechanical work were calculated and averaged within groups showing prominent differences between groups in all parameters. To the best of our knowledge, this is the first work explicitly looking into the kinetics of Duchenne gait in patients with CP, clinically known as compensation for unloading hip abductor muscles. The results show that excessive lateral trunk motion may indeed be an extremely effective compensation mechanism to unload the hip abductors in single limb stance but for the price of a drastic increase in demand on trunk muscle effort and work.
Available online 7 September 2017
Gesehen am 19.06.2018